Surgical Aspects of Primary Hyperparathyroidism. (17th October 2022) - Perrier, Nancy; Lang, Brian H.; Farias, Leonardo Costa Bandeira; Poch, Leyre Lorente; Sywak, Mark; Almquist, Martin; Vriens, Menno R.; Yeh, Michael W.; Shariq, Omair; Duh, Quan‐Yang; Yeh, Randy; Vu, Thinh; et al.
ABSTRACT: Parathyroidectomy (PTX) is the treatment of choice for symptomatic primary hyperparathyroidism (PHPT). It is also the treatment of choice in asymptomatic PHPT with evidence for target organ involvement. This review updates surgical aspects of PHPT and proposes the following definitions based on international expert consensus: selective PTX (and reasons for conversion to an extended procedure), bilateral neck exploration for non‐localized or multigland disease, subtotal PTX, total PTX with immediate or delayed autotransplantation, and transcervical thymectomy and extended en bloc PTX for parathyroid carcinoma. The systematic literature reviews discussed covered (i) the use of intraoperative PTH (ioPTH) for localized single‐gland disease and (ii) the management of low BMD after PTX. Updates based on prospective observational studies are presented concerning PTX for multigland disease and hereditary PHPT syndromes, histopathology, intraoperative adjuncts, localization techniques, perioperative management, "reoperative" surgery and volume/outcome data. Postoperative complications are few and uncommon (<3%) in centers performing over 40 PTXs per year. This review is the first global consensus about surgery in PHPT and reflects the current practice in leading endocrine surgery units worldwide. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).